Lithium manganese iron phosphate positive electrode material, preparation method thereof and lithium ion battery

Through two-step sintering method and doping treatment, lithium manganese iron phosphate positive electrode material with high voltage, high capacity and high compaction density was prepared, solving the problems of low electronic conductivity and lithium ion diffusion coefficient of existing materials.

CN119797304APending Publication Date: 2025-04-11WANHUA CHEM GRP BATTERY TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311314680.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

At this stage, the electronic conductivity and lithium ion diffusion coefficient of the lithium manganese phosphate cathode material are low, which affects its electrochemical properties.

Method used

A two-step sintering method is used to prepare lithium manganese iron phosphate positive electrode material. The first sintering temperature is 800℃-900℃, and the second sintering temperature is 600℃-800℃. During the sintering process, doped raw materials and titanium sources are introduced for calcination to form a structure of carbon and titanium co-coated.

Benefits of technology

Through this method, a good balance can be achieved in the initial discharge capacity, average voltage and compaction density, and the overall performance of the positive electrode material can be significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797304A_ABST
    Figure CN119797304A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and provides a lithium iron manganese phosphate positive electrode material, a preparation method thereof and a lithium ion battery, and the lithium iron manganese phosphate positive electrode material prepared by the preparation method disclosed by the invention is favorable for achieving good balance in the aspects of initial discharge capacity, average voltage, compaction density and the like; and better comprehensive performance is obtained. The preparation method comprises the following steps: S1, preparing a mixed precursor from precursor raw materials, wherein the precursor raw materials comprise a lithium source, an iron source, a manganese source, a phosphorus source and a carbon source; and S2, sintering the mixed precursor to obtain the lithium iron manganese phosphate positive electrode material, wherein the sintering comprises first sintering and second sintering which are carried out in sequence; the temperature of the first sintering is 800-900 DEG C, the temperature of the second sintering is 600-800 DEG C, and the temperature of the first sintering is higher than the temperature of the second sintering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron manganese phosphate positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] The increasing demand for clean energy in today's society has driven the release of lithium iron phosphate production capacity. However, as the energy density requirements of electric vehicles increase, lithium iron phosphate cathode materials seem to be unable to meet the requirements. Therefore, it is urgent to develop the next generation of high energy density cathode material batteries.

[0003] In the current product development, lithium manganese phosphate (LiMnPO4, LMP) cathode material has great development potential, which can be attributed to the fact that lithium manganese phosphate cathode material has a higher voltage platform of 4.10V (vs Li+ / Li), and its gram capacity is comparable to that of lithium iron phosphate material. However, lithium manganese phosphate cathode material also has a pain point, namely, low electronic conductivity (~10 -10 Scm -1 ), and the lithium ion diffusion coefficient is low. Doping Fe in lithium manganese phosphate can alleviate the 3+ The induced Jiang-Taylor effect stabilizes the crystal structure of the material and enhances the electron and lithium ion conduction of the positive electrode material.

[0004] However, there are still many difficulties to be overcome in preparing high-performance lithium manganese iron phosphate positive electrode materials. Summary of the invention

[0005] The present invention provides a lithium iron manganese phosphate positive electrode material and a preparation method thereof and a lithium ion battery. The lithium iron manganese phosphate positive electrode material prepared by the preparation method of the present invention is conducive to achieving a good balance in terms of initial discharge capacity, average voltage and compaction density, thereby obtaining better comprehensive performance.

[0006] To achieve the purpose, the present invention provides the following technical solutions:

[0007] In one aspect, the present invention provides a method for preparing a lithium manganese iron phosphate positive electrode material, the preparation method comprising the following steps:

[0008] S1. Preparing a mixed precursor using precursor raw materials, wherein the precursor raw materials include a lithium source, an iron source, a manganese source, a phosphorus source and a carbon source;

[0009] S2, sintering the mixed precursor to obtain the lithium manganese iron phosphate positive electrode material;

[0010] The sintering includes a first sintering and a second sintering performed sequentially; the temperature of the first sintering is 800°C-900°C; the temperature of the second sintering is 600°C-800°C, preferably 640-800°C, and the temperature of the first sintering is higher than the temperature of the second sintering.

[0011] Preferably, the step S1 comprises:

[0012] The precursor raw material is dispersed in a solvent to obtain a mixed suspension, and then a first drying is performed to obtain the mixed precursor; the temperature of the first drying is, for example, 200-300° C.;

[0013] Preferably, after the first drying, the material obtained by the first drying is subjected to a first cleaning treatment with a first surfactant solution; preferably, the first cleaning treatment includes dispersing the material obtained by the first drying with the first surfactant solution, then filtering and subjecting the obtained filter residue to a second drying; the temperature of the second drying is, for example, 100-300° C.;

[0014] More preferably, the first surfactant is selected from one or more of sulfonated lignin, sodium dodecylbenzene sulfonate, and sulfosalicylic acid, and the concentration of the first surfactant solution is preferably 0.3-0.7 wt %.

[0015] Preferably, the step S2 further comprises: performing a second cleaning treatment on the sintered material using a second surfactant solution;

[0016] Preferably, the second cleaning treatment includes sequentially crushing, cleaning and third drying the sintered material, and the temperature of the third drying is, for example, 200-300°C;

[0017] Further preferably, the cleaning comprises dispersing the crushed material with the second surfactant solution and then filtering;

[0018] Preferably, the second surfactant is selected from at least one of sulfonated lignin, sodium dodecylbenzene sulfonate, and sulfosalicylic acid, and the concentration of the second surfactant solution is preferably 0.3-0.7 wt%.

[0019] Preferably, the step S2 further comprises: after the second cleaning treatment, mixing the obtained material with a titanium source and calcining them to obtain a carbon and titanium co-coated lithium manganese iron phosphate positive electrode material.

[0020] Preferably, the step S2 further includes:

[0021] The sintered material is mixed with a titanium source and calcined.

[0022] Preferably, the calcination is carried out in an inert atmosphere, the calcination temperature is 200-500° C., preferably 250-350° C., and the calcination time is preferably 5-8 h;

[0023] Preferably, the mass proportion of the titanium element provided by the titanium source in the lithium manganese iron phosphate positive electrode material is 500ppm-3000ppm;

[0024] Preferably, the titanium source is selected from one or more of metatitanic acid, titanium dioxide, tetrabutyl titanate, and titanium isopropoxide.

[0025] Preferably, the first sintering time is 5-10 hours, preferably 5 hours to 7 hours, and the second sintering time is 5 hours to 8 hours;

[0026] The sintering preferably further comprises heat preservation sintering, which is performed before the first sintering; the temperature of the heat preservation sintering is 300° C.-550° C., and the time of the heat preservation sintering is preferably 2 h-4 h;

[0027] Preferably, the sintering is carried out in an inert atmosphere;

[0028] Preferably, the heating rates for the heat preservation sintering and the first sintering are 5° C. / min-10° C. / min respectively.

[0029] Preferably, in the precursor raw material, the molar ratio of Fe element to Mn element is (1-a): a, wherein 0.1≤a≤0.9; preferably, the molar ratio of Fe element to Mn element is 0.6-0.7;

[0030] In the precursor raw material, the ratio of the amount of the Li element to the sum of the amounts of the transition metal elements in the precursor raw material is (1-1.08): 1;

[0031] In the precursor raw material, the ratio of the sum of the amounts of Fe and Mn to the sum of the amounts of each transition metal element in the precursor raw material is 0.98-1;

[0032] In the precursor raw material, the ratio of the sum of the amounts of Mn and Fe to the amount of P is 0.97-1.00;

[0033] In the precursor raw material, the ratio of the mass of Fe element to the mass of the carbon source is 0.8-1.2.

[0034] Preferably, in step S1, the precursor raw material further includes a doping raw material, and the doping raw material is selected from at least one of a zirconium source, a magnesium source, an aluminum source, a titanium source, a tungsten source, a molybdenum source, and a niobium source;

[0035] Preferably, the mass proportion of the metal element provided by the doping raw material in the mixed precursor is 500ppm-3000ppm;

[0036] Preferably, the zirconium source includes at least one of ammonium zirconium carbonate, zirconium hydroxide, zirconium carbonate and zirconium oxide.

[0037] The lithium source preferably includes at least one of lithium carbonate, lithium hydroxide, lithium oxide, lithium oxalate, lithium acetate, lithium phosphate, and lithium dihydrogen phosphate;

[0038] The iron source preferably includes at least one of ferric phosphate, ferric hydroxide, ferric oxide, ferric acetate, and ferric citrate;

[0039] The manganese source preferably includes at least one of manganese carbonate, manganese hydroxide, manganese acetate, and manganese oxalate;

[0040] The phosphorus source preferably includes at least one of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, iron phosphate, lithium phosphate, and lithium dihydrogen phosphate;

[0041] The carbon source preferably includes at least one of glucose, fructose, sucrose, ethylene glycol, polyethylene glycol, polyvinyl alcohol, isopropanol, citric acid, and ascorbic acid.

[0042] Preferably, the carbon content in the lithium manganese iron phosphate positive electrode material is 0.5wt%-10wt%.

[0043] Another aspect of the present invention provides a lithium manganese iron phosphate positive electrode material, which is prepared by the preparation method described above.

[0044] The present invention also provides a lithium ion battery, wherein the positive electrode of the lithium ion battery comprises the lithium iron manganese phosphate positive electrode material described above.

[0045] The technical solution provided by the present invention has the following beneficial effects:

[0046] In the process of preparing lithium iron manganese phosphate positive electrode material of the present invention, when sintering the mixed precursor, the first sintering is first carried out at a higher temperature of 800°C-900°C, and then the second sintering is carried out at a lower temperature of 600°C-800°C, and the first sintering temperature is controlled to be higher than the second sintering temperature, which is conducive to obtaining a positive electrode material that can well balance comprehensive performance such as high voltage, high capacity and high compaction density. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 Shown is a TEM image of a lithium manganese iron phosphate positive electrode material prepared in one embodiment;

[0048] Figure 2 Shown are the SEM results in Example 1;

[0049] Figure 3 Shown are the X-ray diffraction spectrum results in Example 1. DETAILED DESCRIPTION

[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The term "and / or" that may be used herein includes any and all combinations of one or more related listed items, for example, A and / or B includes (A and B) and (A or B).

[0051] The terms "first", "second", "third", etc. mentioned or may be mentioned in this specification are for descriptive purposes only and cannot be understood as indicating or implying relative importance. In the text, when a numerical range is described in this text, unless otherwise specified, the range is intended to include its end values ​​and all integers and fractions within the range.

[0052] The present invention provides a method for preparing a lithium manganese iron phosphate positive electrode material, which mainly comprises the following steps:

[0053] S1. Preparing a mixed precursor using precursor raw materials, wherein the precursor raw materials include a lithium source, an iron source, a manganese source, a phosphorus source and a carbon source;

[0054] S2, sintering the mixed precursor to obtain a lithium manganese iron phosphate positive electrode material;

[0055] Wherein, the sintering includes a first sintering and a second sintering which are carried out successively; the temperature of the first sintering is 800℃-900℃, for example, 800, 820, 850, 870, 900℃, etc., and the temperature of the second sintering is 600℃-800℃, for example, 600, 620, 640, 680, 700, 720, 750, 770, 800℃, etc., preferably 640-800℃, and the temperature of the first sintering is higher than the temperature of the second sintering.

[0056] The inventors found that in the process of preparing lithium manganese iron phosphate positive electrode material, when the mixed precursor is sintered, the first sintering is first performed at a higher temperature of 800℃-900℃, and then the second sintering is performed at a lower temperature of 600℃-800℃, and the first sintering temperature is controlled to be higher than the second sintering temperature, so that the positive electrode material can grow rapidly during the first sintering process, making the particle distribution structure chaotic, and then entering the second sintering at a slightly lower temperature, which can provide internal energy to repair the internal structure of the material, which is conducive to obtaining a positive electrode material with high voltage, high capacity and high compaction density. Specifically, the first sintering and the second sintering are performed continuously, that is, the second sintering is directly performed after the first sintering is completed.

[0057] In some embodiments, step S1 specifically includes: dispersing the precursor raw material in a solvent to obtain a mixed suspension, and then performing a first drying to obtain the mixed precursor, wherein the temperature of the first drying is, for example, 200-300°C, specifically 200°C, 250°C or 300°C. Specifically, the specific selection of the solvent is easily determined by those skilled in the art based on the precursor raw material, and the types of solvents conventionally used in the art can be used, such as water as a solvent, ethylene glycol and / or isopropanol and / or polyethylene glycol as a solvent, etc. In some examples, for example, precursor raw materials such as a lithium source, an iron source, a manganese source, a phosphorus source, and a carbon source are mixed and dispersed with water to obtain a mixed suspension, and then the mixed suspension is dried to obtain a mixed precursor. In some examples, for example, a lithium source (such as lithium carbonate, etc.) and a phosphorus source (such as phosphoric acid, etc.) are mixed and stirred with ethylene glycol or polyethylene glycol to obtain a suspension, and other precursor raw materials are mixed with water to obtain an aqueous solution, and then the two are mixed and stirred (for example, stirred for 30 minutes) to obtain a mixed suspension, and then dried to obtain a mixed precursor. When preparing a mixed precursor, there is no particular restriction on the specific dispersion operation of each precursor raw material and the specific amount of solvent used, which is based on the ability to evenly disperse the components in the precursor raw material.

[0058] Specifically, the drying method of the aforementioned first drying is not particularly limited, and may be, for example, spray drying, vacuum drying, fluidized bed drying, hot air drying, freeze drying, etc.; wherein the spray drying is, for example, ultrasonic atomization drying. When ultrasonic atomization drying is adopted, for example, the frequency of the ultrasonic atomizer used is 1.5MHz-1.8MHz, the flow rate of the droplets is 2L / min-5L / min, and the inlet temperature is 200℃-300℃.

[0059] In some preferred embodiments, after the first drying, the material obtained by the first drying is also subjected to a first cleaning treatment with a first surfactant solution. When preparing a mixed precursor, before sintering, the first cleaning treatment is performed with the above-mentioned first surfactant solution to remove impurities. Preferably, the first cleaning treatment preferably includes dispersing the material obtained by the first drying with a first surfactant solution, then filtering and subjecting the obtained filter residue to a second drying; the first cleaning treatment is carried out in this preferred manner, which is conducive to the uniform dispersion of the precursor particles, and the first surfactant (carbon-containing substance) can be evenly coated on the surface of the particles, which is conducive to obtaining a carbon-coated lithium manganese iron phosphate positive electrode material after the mixed precursor is sintered, which is conducive to improving the performance of the positive electrode material. The filtration mentioned therein is, for example, suction filtration. The temperature of the second drying is, for example, 100-300°C, specifically 100°C, 150°C, 200°C, 250°C or 300°C. Specifically, it can be placed in an oven for a second drying so that the final product is completely converted into a mixed precursor in a powder state. Preferably, the first surfactant is selected from one or more of sulfonated lignin, sodium dodecylbenzene sulfonate, and sulfosalicylic acid, and the concentration of the first surfactant solution is preferably 0.3-0.7wt%. The first surfactant solution is, for example, an aqueous solution. The amount of the first surfactant solution is based on at least being able to well disperse the material obtained by the first drying. In some embodiments, the amount of the first surfactant is 0.01-0.2 times the mass of the material obtained by the first drying, for example, 0.01, 0.05, 0.1, 0.15, 0.2 times.

[0060] In some preferred embodiments, the step S2 further includes: subjecting the sintered material to a second cleaning treatment with a second surfactant solution; preferably, the second cleaning treatment includes sequentially crushing, cleaning and third drying the sintered material, and the temperature of the third drying is, for example, 200-300°C. After sintering, the above-mentioned second cleaning treatment is carried out to facilitate the removal of water-soluble impurities in the material. Preferably, the cleaning in the second cleaning treatment includes dispersing the crushed material with a second surfactant solution and then filtering; the inventors found that the second cleaning treatment using this preferred method can evenly wrap the second surfactant on the surface of the crushed powder particles to prevent agglomeration, and the second surfactant can continue to form a carbon coating layer during the subsequent calcination treatment; the above-mentioned second cleaning treatment is used to further improve the performance of the positive electrode material and improve the conductivity of the positive electrode material. In some embodiments, the second surfactant is preferably selected from at least one of sulfonated lignin, sodium dodecylbenzene sulfonate, and sulfosalicylic acid, and the concentration of the second surfactant solution is preferably 0.3-0.7wt%, and the second surfactant solution is, for example, an aqueous solution. The amount of the second surfactant solution used is based on at least being able to well disperse the pulverized material. In some embodiments, the amount of the second surfactant used is 0.01-0.2 times the mass of the pulverized material, for example 0.01, 0.05, 0.1, 0.15, 0.2 times.

[0061] In a more preferred embodiment, the first cleaning treatment is performed in step S1, and the second cleaning treatment is performed in step S2, which is beneficial to further improve the comprehensive performance of the obtained positive electrode material, and further improve the discharge capacity, average voltage and compaction density of the obtained positive electrode material.

[0062] In some preferred embodiments, step S2 further comprises: mixing the sintered material with a titanium source and calcining them to obtain a carbon and titanium co-coated lithium iron manganese phosphate positive electrode material. In a more preferred embodiment, the sintered material is subjected to the aforementioned second cleaning treatment and then mixed with a titanium source and calcined. By introducing a titanium source for calcination to form a carbon and titanium co-coated lithium iron manganese phosphate positive electrode material, the conductivity of the positive electrode material is further improved, and a positive electrode material with better performance is obtained.

[0063] Preferably, the calcination is carried out in an inert atmosphere, and the calcination temperature is 200-500°C, for example, it can be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C or 500°C, preferably the calcination temperature is 250-350°C; the calcination time is preferably 5-8h, for example, it can be 5h, 6h, 7h or 8h. Preferably, the titanium source used for the above calcination has a mass proportion of 500ppm-3000ppm of titanium element in the lithium manganese iron phosphate positive electrode material, for example, it can be 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm or 3000ppm. Preferably, the titanium source is selected from one or more of metatitanic acid, titanium dioxide, tetrabutyl titanate, and titanium isopropoxide.

[0064] In some embodiments, in the precursor raw material, the molar ratio of Fe element to Mn element is (1-a): a, wherein 0.1≤a≤0.9, and the molar ratio may be, for example, 0.9:0.1, 0.8:0.2, 0.6:0.4, 0.5:0.5, 0.3:0.7 or 0.1:0.9. Preferably, the molar ratio of Fe element to Mn element is 0.6-0.7. In the precursor raw material, the ratio of the molar ratio of Li element to the sum of the molar ratios of the transition metal elements in the precursor raw material is (1-1.08): 1, for example, 1:1, 1.02:1, 1.04:1, 1.05:1, 1.06:1 or 1.08:1. In the precursor raw material, the ratio of the sum of the amount of Fe and Mn elements to the sum of the amount of each transition metal element in the precursor raw material is 0.98-1, such as 0.98, 0.99, 1, etc.; in the precursor raw material, the ratio of the sum of the amount of Mn and Fe elements to the amount of P element is 0.97-1, such as 0.97, 0.98, 0.99, 1, etc.; in the precursor raw material, the ratio of the mass of Fe element to the mass of carbon source is 0.8-1.2. In some embodiments, the amount of carbon source is 20-40% of the mass of iron phosphate, such as 34%.

[0065] In some preferred embodiments, in step S1, the precursor raw material further includes a doping raw material, and the doping raw material is selected from at least one of a zirconium source, a magnesium source, an aluminum source, a titanium source, a tungsten source, a molybdenum source, and a niobium source. By introducing a doping substance, the structural stability of the positive electrode material can be improved, and the electrochemical performance of the positive electrode material can be further improved.

[0066] Preferably, the mass proportion of the metal element (such as zirconium, magnesium, aluminum, titanium, tungsten, molybdenum and / or niobium) provided by the doping raw material in the mixed precursor is 500ppm-3000ppm. Taking the doping raw material as a zirconium source as an example, the mass proportion of the zirconium element provided by the zirconium source in the mixed precursor is preferably 500ppm-3000ppm, for example, it can be 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm or 3000ppm. Preferably, the zirconium source includes at least one of ammonium zirconium carbonate, zirconium hydroxide, zirconium carbonate and zirconium oxide, more preferably ammonium zirconium carbonate.

[0067] The magnesium source may be, for example, one or more of magnesium carbonate, magnesium oxide, magnesium fluoride, etc.; the aluminum source may be, for example, one or more of aluminum oxide, aluminum carbonate, etc.; the molybdenum source may be, for example, one or more of molybdenum trioxide, molybdic anhydride, etc.; the niobium source may be, for example, one or more of niobium pentoxide, niobic acid, niobium pentafluoride, etc.

[0068] In some preferred embodiments, the aforementioned doping raw material is introduced into the precursor raw material in step S1, and a titanium source is introduced after sintering in step S2 for the aforementioned calcination, which is beneficial to further significantly improve the electrochemical performance of the positive electrode material.

[0069] In the present invention, the lithium source, iron source, manganese source, phosphorus source, carbon source, etc. used can adopt the corresponding raw materials conventionally applicable in the art, without particular limitation. In some embodiments, the lithium source preferably includes at least one of lithium carbonate, lithium hydroxide, lithium oxide, lithium oxalate, lithium acetate, lithium phosphate, and lithium dihydrogen phosphate. In some embodiments, the iron source preferably includes at least one of ferric phosphate, ferric hydroxide, ferric oxide, ferric acetate, and ferric citrate. In some embodiments, the manganese source preferably includes at least one of manganese carbonate, manganese hydroxide, manganese acetate, and manganese oxalate. In some embodiments, the phosphorus source preferably includes at least one of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, iron phosphate, lithium phosphate, and lithium dihydrogen phosphate. In some embodiments, the carbon source preferably includes at least one of glucose, fructose, sucrose, ethylene glycol, polyethylene glycol, polyvinyl alcohol, isopropanol, citric acid, and ascorbic acid.

[0070] In some embodiments, the carbon source specifically includes an alcohol carbon source, and also includes at least one of a sugar carbon source (such as glucose, fructose, sucrose, etc.) and an acid carbon source (such as citric acid, ascorbic acid, etc.). For example, in some embodiments, an alcohol carbon source and a sugar carbon source may be included at the same time. Alcohol carbon sources include, for example, ethylene glycol, isopropanol, etc. These alcohol carbon sources can be used as solvents to disperse other precursor raw materials (such as dispersed lithium sources, phosphorus sources, etc.). In some embodiments, the ratio of the mass of iron element to the mass of the carbon source is 0.8-1.2.

[0071] In step S2, the temperature for the first sintering is 800°C-900°C, for example, 800°C, 820°C, 850°C, 880°C or 900°C; the time for the first sintering can be 5-10h, more preferably 5h-7h, for example, 5h, 6h or 7h. In step S2, the temperature for the second sintering is 600°C-800°C, for example, 600°C, 620°C, 650°C, 680°C, 700°C, 720°C, 750°C, 780°C or 800°C, and the temperature of the second sintering needs to be lower than the temperature of the first sintering; the time for the second sintering can be 5h-8h, for example, 5h, 6h, 7h or 8h.

[0072] In some preferred embodiments, in step S2, the sintering further includes heat preservation sintering, which is performed before the first sintering; the temperature of the heat preservation sintering is 300°C-550°C, for example, 300°C, 320°C, 350°C, 400°C, 480°C, 500°C, 520°C or 550°C. The time of the heat preservation sintering is, for example, 2h-4h, for example, 2h, 3h or 4h.

[0073] Furthermore, the sintering in the present invention is performed in an inert atmosphere.

[0074] In the present invention, the gas used to provide the inert atmosphere is, for example, nitrogen, argon, helium, etc.

[0075] In some preferred embodiments, the heating rates for the heat preservation sintering and the first sintering are 5°C / min-10°C / min, for example, 5°C / min, 6°C / min, 8°C / min or 10°C / min.

[0076] In a preferred embodiment of the present invention, the carbon content in the prepared lithium manganese iron phosphate positive electrode material is 0.5wt%-10wt%, for example, 0.5wt%, 1wt%, 2wt%, 5wt%, 7wt%, 10wt% and the like.

[0077] The second aspect of the present invention also provides a lithium manganese iron phosphate positive electrode material, which is prepared by the preparation method described above.

[0078] The lithium iron manganese phosphate positive electrode material prepared by the present invention is particularly suitable for use in lithium ion batteries. Therefore, the present invention also provides a lithium ion battery, the positive electrode of which includes the lithium iron manganese phosphate positive electrode material described above.

[0079] For ease of understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples. Where specific experimental steps or conditions are not indicated in the examples, the operation or conditions of the corresponding conventional experimental steps in the art can be carried out. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0080] Description of the test method:

[0081] The contents of metal elements were determined by ICP (inductively coupled plasma) and atomic absorption spectroscopy.

[0082] The compaction density tester (Shenzhen Sansi Instrument Model UTM7305) was used to test the compaction density of the material with a pressure of 3t.

[0083] The carbon content of the positive electrode material is tested using a carbon-sulfur analyzer.

[0084] Example 1

[0085] A lithium manganese iron phosphate positive electrode material, the preparation method comprises the following steps:

[0086] (1) 188 mg of lithium carbonate powder was mixed with 57 mg of PEG6000 (polyethylene glycol 6000, Wanhua Chemical) solution and stirred for 1 h, and 344 mg of phosphoric acid aqueous solution (concentration 85 wt%) was added dropwise to the stirred suspension, and the mixture was stirred for 30 min after the addition was completed to obtain a lithium carbonate / phosphoric acid / PEG suspension. At the same time, 300 mg of iron phosphate, 363 mg of manganese carbonate, 30.11 mg of 20% ammonium zirconium carbonate aqueous solution and 39 mg of sucrose were added to 3 ml of deionized water and mixed evenly to obtain a mixed aqueous solution. The aqueous solution was then continuously added to the lithium carbonate / phosphoric acid / PEG suspension, and stirred for 30 min at room temperature to obtain a mixed suspension.

[0087] (2) The mixed suspension of step (1) was spray dried, with an inlet temperature of 300°C, an outlet temperature of 100°C, an atomization frequency of 1.6 MHZ, and a droplet flow rate of 0.2 L / min. The obtained powder material was transferred to a 0.5 wt% sodium dodecylbenzene sulfonate aqueous solution, and the obtained mixed solution had a solid content of 40 wt%. The mixture was stirred at a stirring speed of 100 rpm for 5 min, and after suction filtration, the obtained filter residue was dried at 200°C, and then passed through a 200 mesh sieve to obtain a powder mixed precursor, in which the mass proportion of zirconium element was 2475 ppm.

[0088] (3) The mixed precursor of step (2) is placed in a sintering furnace under the protection of a nitrogen atmosphere, and the temperature is increased to 550°C at a heating rate of 5°C / min and then kept at this temperature for 4 hours. Subsequently, the temperature is increased to 800°C at a heating rate of 5°C / min and kept at this temperature for 6 hours for the first sintering. After that, the temperature is adjusted down to 680°C and kept at this temperature for 6 hours for the second sintering. After cooling and crushing, an initial lithium manganese iron phosphate compound is obtained.

[0089] (4) The product obtained in step (3) is transferred to a sodium dodecylbenzene sulfonate aqueous solution with a concentration of 0.5wt%, and the solid content of the obtained mixed solution is 30wt%. The mixture is stirred at a stirring speed of 100rpm for 5min, and after suction filtration, the obtained filter residue is dried at 200°C and then passed through a 200-mesh sieve. Then, it is fully mixed with 3.55mg of nano-scale metatitanic acid, and then calcined in a nitrogen protective atmosphere at a calcination temperature of 300°C for 6h to finally obtain a carbon and titanium co-coated lithium manganese iron phosphate positive electrode material, whose chemical formula is C / Li 1.02 Fe 0.4 Mn 0.6 PO4Zr 0.0005 Ti 0.002 .

[0090] The obtained positive electrode material has a carbon content of 1.65wt%, and a mass proportion of titanium element of 2201ppm.

[0091] Figure 1 This is a TEM image of the lithium manganese iron phosphate positive electrode material prepared in this example. It can be clearly seen from the image that there is a very thin coating layer on the surface of the material.

[0092] The X-ray diffraction spectrum of the calcined powder of this example was obtained by high-sensitivity X-ray diffraction using Cu-Kα rays. The measurement conditions were an accelerating voltage of 50 KV, an accelerating current of 250 mA, a scanning speed of 2° / min, and a step angle of 0.02°. The results are shown in Figure 3 , the result can be determined to be lithium manganese iron phosphate.

[0093] The positive electrode material prepared in Example 1 was observed using a SEM (scanning electron microscope). Figure 2 It was found that the obtained positive electrode material powder was composed of single crystal morphology particles and secondary large particles composed of primary particles.

[0094] Example 2 (without adding doping raw materials)

[0095] This embodiment provides a lithium manganese iron phosphate positive electrode material, and the preparation method thereof is carried out with reference to that of Embodiment 1, except that: in step (1), no 20% by mass aqueous solution of ammonium zirconium carbonate is added.

[0096] Example 3 (calcination without adding titanium source)

[0097] This embodiment provides a lithium manganese iron phosphate positive electrode material, and the preparation method thereof is carried out with reference to that of Embodiment 1, except that: in step (4), no nano-sized metatitanic acid is added for mixing.

[0098] Example 4 (calcination without adding doping raw material + without adding titanium source)

[0099] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is carried out in accordance with the method of embodiment 1, except that: in step (1), no 20% by mass ammonium zirconium carbonate aqueous solution is added, and in step (4), no nano-sized metatitanic acid is added for mixing.

[0100] Example 5 (lowering the second sintering temperature)

[0101] This embodiment provides a lithium manganese iron phosphate positive electrode material, and the preparation method thereof is carried out with reference to that of Embodiment 1; the difference being that in step (3), the temperature for the first sintering is 800° C., and the temperature for the second sintering is 600° C.

[0102] Example 6 (Extending the time of the first sintering)

[0103] This embodiment provides a lithium manganese iron phosphate positive electrode material, and the preparation method thereof is carried out with reference to that of Embodiment 1, except that: the first sintering time at 800° C. is extended to 10 h.

[0104] Example 7 (lowering the calcination temperature)

[0105] This embodiment provides a lithium manganese iron phosphate positive electrode material, and the preparation method thereof is carried out with reference to that of Embodiment 1, except that in step (4), the calcination temperature is 200° C. and the calcination is kept for 6 hours.

[0106] Comparative Example 1

[0107] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is carried out according to Example 1, except that: in step (3), the temperature is raised to 550°C at a heating rate of 5°C / min and kept warm for 4 hours, and then the temperature is further raised to 700°C and kept warm for 6 hours, and then directly cooled and crushed; then step (4) is entered.

[0108] Comparative Example 2

[0109] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is carried out according to Example 1, except that: after spray drying in step (2), it is not transferred to a 0.5wt% sodium dodecylbenzene sulfonate aqueous solution, but directly performs the sintering operation of step (3); and in step (4), it is also not transferred to a 0.5wt% sodium dodecylbenzene sulfonate aqueous solution, but directly mixed with nano-sized metatitanic acid and calcined.

[0110] Comparative Example 3

[0111] The present comparative example provides a lithium manganese iron phosphate positive electrode material, and the preparation method thereof is carried out in accordance with Example 1, except that: in step (3), the mixed precursor of step (2) is placed in a sintering furnace under the protection of a nitrogen atmosphere, the temperature is increased to 550°C at a heating rate of 5°C / min, and then the temperature is kept at this temperature for sintering for 4 hours, and then the temperature is increased to 800°C at a heating rate of 5°C / min and kept at this temperature for 6 hours for the first sintering, and then the temperature is adjusted to 840°C and kept at this temperature for 6 hours for the second sintering.

[0112] Comparative Example 4

[0113] The present comparative example provides a lithium manganese iron phosphate positive electrode material, and the preparation method thereof is carried out in accordance with Example 1, except that: in step (3), the mixed precursor of step (2) is placed in a sintering furnace under the protection of a nitrogen atmosphere, the temperature is increased to 550°C at a heating rate of 5°C / min, and then the temperature is kept at this temperature for sintering for 4 hours, and then the temperature is increased to 1000°C at a heating rate of 5°C / min and kept at this temperature for 6 hours for the first sintering, and then the temperature is adjusted down to 500°C and kept at this temperature for 6 hours for the second sintering.

[0114] Comparative Example 5

[0115] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is carried out with reference to Example 1, except that: in step (4), the operation of transferring the product obtained in step (3) to a 0.5wt% sodium dodecylbenzene sulfonate aqueous solution is omitted, and the product is directly mixed and calcined with nano-sized titanic acid.

[0116] The positive electrode materials prepared in the above Examples 1-7 and Comparative Examples 1-5 were made into button batteries, and their electrochemical properties were tested. The preparation method of the button batteries includes the following steps:

[0117] (1) A positive electrode material, SURPER P conductive carbon black, and polytetrafluoroethylene powder were mixed in a weight ratio of 90:5:5, and toluene was added while mixing and drying to obtain a positive electrode plate with a thickness of 150 μm;

[0118] (2) A 20 μm thick aluminum foil was used as the positive electrode collector, a 25 μm thick porous polypropylene was used as the separator, a 500 μm thick metal lithium foil was used as the negative electrode, a 20 μm nickel platinum was used as the negative electrode collector, and a 1 mol / L LiPF6 / EC+DEC electrolyte (i.e., the solute of the electrolyte was LiPF6, and the solvent was a mixed solvent of ethylene carbonate and diethyl carbonate in a mass ratio of 1:1) was used to assemble a button cell in an argon glove box.

[0119] When conducting electrochemical tests, at 25°C, the button cell was charged to 4.3V at a load current of 75mA per 1g of positive electrode material, and then discharged to 2.0V at a load current of 75mA per 1g of positive electrode material to obtain the initial discharge capacity; and then the battery was subjected to 15 charge and discharge cycle tests (1C / 1C charge and discharge, voltage range 2-4.3V). The battery performance corresponding to the positive electrode materials prepared in the examples and comparative examples is shown in Table 1.

[0120] Table 1

[0121]

[0122]

[0123] It can be seen from the experimental results in Table 1 that, compared with Example 1, Comparative Example 1 omitted the first sintering under the same other conditions, and as a result, the initial discharge capacity, average voltage and compaction density of the obtained positive electrode material were significantly reduced.

[0124] Compared with Example 1, Comparative Example 2 does not perform the first cleaning treatment and the second cleaning treatment under the same conditions, and the initial discharge capacity, average voltage and compaction density of the obtained positive electrode material are significantly reduced. From the comparison of Comparative Example 5, Comparative Example 2 and Example 1, Comparative Example 5 performs the first cleaning treatment and does not perform the second cleaning treatment under the same conditions, and its comprehensive performance is better than Comparative Example 2, but significantly inferior to Example 1.

[0125] Compared with Example 1, in Comparative Examples 3-4, under the condition that other conditions are the same, the first sintering and the second sintering do not meet the requirements of "the temperature of the first sintering is 800℃-900℃; the temperature of the second sintering is 600℃-800℃, and the temperature of the first sintering is higher than the temperature of the second sintering". As a result, the comprehensive performance of the obtained positive electrode material is significantly inferior to that of Example 1, with a significantly reduced initial discharge capacity, and the average voltage is also reduced.

[0126] From the comparison of Examples 1-7, it can be seen that in Example 1, during the preparation of the positive electrode material, the doping raw material is introduced, and the sintering time is controlled to be 5-7h during the first sintering at 800-900°C, and the temperature is controlled to be 640-800°C during the second sintering. After sintering, a titanium source is introduced for mixed calcination, and the calcination temperature is controlled to be between 250-350°C. The prepared positive electrode material has better comprehensive performance, and can take into account better initial discharge capacity, average voltage, cycle performance and compaction density.

[0127] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The preparation method comprises the following steps: S1. Preparing a mixed precursor using precursor raw materials, wherein the precursor raw materials include a lithium source, an iron source, a manganese source, a phosphorus source and a carbon source; S2, sintering the mixed precursor to obtain the lithium manganese iron phosphate positive electrode material; The sintering includes a first sintering and a second sintering performed sequentially; the temperature of the first sintering is 800°C-900°C; the temperature of the second sintering is 600°C-800°C, preferably 640-800°C, and the temperature of the first sintering is higher than the temperature of the second sintering.

2. The preparation method according to claim 1, characterized in that: The step S1 comprises: The precursor raw material is dispersed in a solvent to obtain a mixed suspension, and then a first drying is performed to obtain the mixed precursor; the temperature of the first drying is, for example, 200-300° C.; Preferably, after the first drying, the material obtained by the first drying is subjected to a first cleaning treatment with a first surfactant solution; preferably, the first cleaning treatment includes dispersing the material obtained by the first drying with the first surfactant solution, then filtering and subjecting the obtained filter residue to a second drying; the temperature of the second drying is, for example, 100-300° C.; More preferably, the first surfactant is selected from one or more of sulfonated lignin, sodium dodecylbenzene sulfonate, and sulfosalicylic acid, and the concentration of the first surfactant solution is preferably 0.3-0.7 wt %.

3. The preparation method according to claim 1 or 2, characterized in that: The step S2 further comprises: performing a second cleaning treatment on the sintered material using a second surfactant solution; Preferably, the second cleaning treatment includes sequentially crushing, cleaning and third drying the sintered material, and the temperature of the third drying is, for example, 200-300°C; Further preferably, the cleaning comprises dispersing the crushed material with the second surfactant solution and then filtering; Preferably, the second surfactant is selected from at least one of sulfonated lignin, sodium dodecylbenzene sulfonate, and sulfosalicylic acid, and the concentration of the second surfactant solution is preferably 0.3-0.7 wt%; Preferably, the step S2 further comprises: after the second cleaning treatment, mixing the obtained material with a titanium source and calcining them to obtain a carbon and titanium co-coated lithium manganese iron phosphate positive electrode material.

4. The preparation method according to any one of claims 1 to 2, characterized in that: The step S2 further comprises: The sintered material is mixed with a titanium source and calcined.

5. The preparation method according to claim 3 or 4, characterized in that: The calcination is carried out in an inert atmosphere, the calcination temperature is 200-500°C, preferably 250-350°C, and the calcination time is preferably 5-8h; Preferably, the mass proportion of the titanium element provided by the titanium source in the lithium manganese iron phosphate positive electrode material is 500ppm-3000ppm; Preferably, the titanium source is selected from one or more of metatitanic acid, titanium dioxide, tetrabutyl titanate, and titanium isopropoxide.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The first sintering time is 5-10 hours, preferably 5-7 hours, and the second sintering time is 5-8 hours; The sintering preferably further comprises heat preservation sintering, which is performed before the first sintering; the temperature of the heat preservation sintering is 300° C.-550° C., and the time of the heat preservation sintering is preferably 2 h-4 h; Preferably, the sintering is carried out in an inert atmosphere; Preferably, the heating rates for the heat preservation sintering and the first sintering are 5° C. / min-10° C. / min respectively.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In the precursor raw material, the molar ratio of Fe element to Mn element is (1-a): a, wherein 0.1≤a≤0.9; preferably, the molar ratio of Fe element to Mn element is 0.6-0.7; In the precursor raw material, the ratio of the amount of the Li element to the sum of the amounts of the transition metal elements in the precursor raw material is (1-1.08): 1; In the precursor raw material, the ratio of the sum of the amounts of Fe and Mn to the sum of the amounts of each transition metal element in the precursor raw material is 0.98-1; In the precursor raw material, the ratio of the sum of the amounts of Mn and Fe to the amount of P is 0.97-1.00; In the precursor raw material, the ratio of the mass of Fe element to the mass of the carbon source is 0.8-1.

2.

8. The preparation method according to any one of claims 1 to 7, characterized in that: In step S1, the precursor raw material further includes a doping raw material, and the doping raw material is selected from at least one of a zirconium source, a magnesium source, an aluminum source, a titanium source, a tungsten source, a molybdenum source, and a niobium source; Preferably, the mass proportion of the metal element provided by the doping raw material in the mixed precursor is 500ppm-3000ppm; Preferably, the zirconium source includes at least one of ammonium zirconium carbonate, zirconium hydroxide, zirconium carbonate and zirconium oxide.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The lithium source preferably includes at least one of lithium carbonate, lithium hydroxide, lithium oxide, lithium oxalate, lithium acetate, lithium phosphate, and lithium dihydrogen phosphate; The iron source preferably includes at least one of ferric phosphate, ferric hydroxide, ferric oxide, ferric acetate, and ferric citrate; The manganese source preferably includes at least one of manganese carbonate, manganese hydroxide, manganese acetate, and manganese oxalate; The phosphorus source preferably includes at least one of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, iron phosphate, lithium phosphate, and lithium dihydrogen phosphate; The carbon source preferably includes at least one of glucose, fructose, sucrose, ethylene glycol, polyethylene glycol, polyvinyl alcohol, isopropanol, citric acid, and ascorbic acid; The carbon content in the lithium manganese iron phosphate positive electrode material is preferably 0.5wt%-10wt%.

10. A lithium manganese iron phosphate positive electrode material, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

11. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery comprises the lithium iron manganese phosphate positive electrode material according to claim 10.